Practical pediatric oncology - D'Angio, Giulio J (Wiley-Liss, 1992)
This book should help the physician in the day-to-day management of children with malignant disease. It contains information helpful in the preparation for differential diagnosis and in the treatment and follow-up of children with cancer. It contains the latest information regarding biological markers including chemical tests and genetic clues and provides, in tabulated format, help in differential diagnosis under each disease heading. Management of each major malignant disease of childhood is provided including the role of multi-model care with details concerning the timing of surgery, radiation therapy, chemotherapy and the doses and schedules of drugs employed. The large target readership for this title includes paediatricians, paediatric oncologists, radiotherapists, paediatric surgeons, pathologists, paediatric nurses, anaesthetists and specialist paramedics involved in treating children with cancer.
Keywords: Neoplasms; nádory; Child; dítě; pediatrie; onkologie